Role of Porphyromonas gingivalis HmuY in Immunopathogenesis of Chronic Periodontitis - P. C. Carvalho-Filho; I. S. Gomes-Filho; R. Meyer; T. Olczak; M. T. Xavier; S. C. Trindade (Hindawi Limited, 2016)
Periodontitis is a multifactorial disease, with participation of bacterial, environmental, and host factors. It results from synergistic and dysbiotic multispecies microorganisms, critical "keystone pathogens," affecting the whole bacterial community. The purpose of this study was to review the role of Porphyromonas gingivalis in the immunopathogenesis of chronic periodontitis, with special attention paid to HmuY. The host response during periodontitis involves the innate and adaptive immune system, leading to chronic inflammation and progressive destruction of tooth-supporting tissues. In this proinflammatory process, the ability of P. gingivalis to evade the host immune response and access nutrients in the microenvironment is directly related to its survival, proliferation, and infection. Furthermore, heme is an essential nutrient for development of these bacteria, and HmuY is responsible for its capture from host heme-binding proteins. The inflammatory potential of P. gingivalis HmuY has been shown, including induction of high levels of proinflammatory cytokines and CCL2, decreased levels of IL-8, and increased levels of anti-HmuY IgG and IgG1 antibodies in individuals with chronic periodontitis. Therefore, the HmuY protein might be a promising target for therapeutic strategies and for development of diagnostic methods in chronic periodontitis, especially in the case of patients with chronic periodontitis not responding to treatment, monitoring, and maintenance therapy.